Deprivation and bronchiolitis. Issue 1 (January 1996) - Spencer, N; Logan, S; Scholey, S; Gentle, S
Abstract : OBJECTIVE: To test the hypothesis that socioeconomic deprivation is associated with an increased risk of admission with clinically suspected bronchiolitis. DESIGN: Case-control study. SETTING: Children under 1 year living in Sheffield in 1989-90. SUBJECTS: 307 children resident in Sheffield admitted to Sheffield hospitals with clinically suspected bronchiolitis between 1 October 1989 and 28 February 1990. METHODS: Children admitted with clinically suspected bronchiolitis were ascertained from laboratory records of nasopharyngeal aspirates cultured for respiratory syncytial virus. Case notes were examined to determine whether these children had required medical intervention and postcode of residence was recorded. Controls were selected from the Sheffield child development study (SCDS) data. Postcodes were converted to electoral wards which were assigned Townsend deprivation index scores. Electoral wards were then categorised by Townsend score into five levels of deprivation. Data on family smoking for cases and controls were extracted from the SCDS. RESULTS: Of the 307 children admitted with suspected bronchiolitis during the study period, 127 required one or more medical intervention. The risk of admission with clinically suspected bronchiolitis and with bronchiolitis requiring medical intervention rose with increasing level of deprivation score of electoral ward of residence. Children living in electoral wards in the two more deprived groups were more than 1.5 times as likely to be admitted (odds ratio (OR) 1.67, 95% confidence interval (CI) 1.25 to 2.24) or admitted requiring a medical intervention (OR 1.74, 95% CI 1.16 to 2.62) than children living in other parts of the city. Similar results were obtained after exclusion of children living in homes classified as smoky by the health visitor. CONCLUSION: Residence in an area of social and material deprivation increases the risk of admission with bronchiolitis even after taking account of parental smoking and when only more severe cases were considered.